2003
DOI: 10.1016/s0925-4773(03)00161-8
|View full text |Cite
|
Sign up to set email alerts
|

Congenital diaphragmatic hernia, kidney agenesis and cardiac defects associated with Slit3-deficiency in mice

Abstract: Slit3 along with Slit1 and Slit2 comprise the Slit family of proteins. The latter two proteins are known to be involved in axon guidance and cell migration during animal development. However, little is know about the functions of Slit3. We created a Slit3-deficient mouse model from an OmniBank ES cell line with a Slit3 allele trapped by insertional mutagenesis to analyze the in vivo functions of this protein. In this model, congenital diaphragmatic hernia is the most obvious phenotype. Herniation was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 39 publications
6
117
0
Order By: Relevance
“…8,23 We extended this finding and observed that Slit3 is expressed and secreted by both ECs and VSMCs, the 2 major cell types of vasculature. We also observed that Robo1 and Robo4 are universally expressed by ECs in various organs (Figure 1).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…8,23 We extended this finding and observed that Slit3 is expressed and secreted by both ECs and VSMCs, the 2 major cell types of vasculature. We also observed that Robo1 and Robo4 are universally expressed by ECs in various organs (Figure 1).…”
Section: Discussionmentioning
confidence: 59%
“…In contrast, Slit3 is widely expressed in the central nervous system and peripheral tissues and organs, such as the developing tongue, kidney, genital ridge, pharynx, umbilical cord vein, atrial wall of heart, lung, and diaphragm. [7][8][9] Consistent with the expression patterns, the authors of mouse genetic studies [8][9][10] have established that Slit1 and Slit2 are essential for neural development, whereas Slit3 is dispensable. Instead, Slit3 is required for diaphragm and kidney genesis, revealing that Slit3 critically regulates non-neuron-related developmental processes.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In vertebrates, Slit/Robo function was also proposed to contribute to the development of the cardiovascular system (Calmont et al, 2009;Liu et al, 2003), although it is still unknown whether this involves a classic, repulsive, mechanism or cadherin-dependent cell adhesion.…”
Section: Regulation Of Cell Adhesionmentioning
confidence: 99%